Penerapan Model Pembelajaran Berbasis Maslah Untuk Meningkatkan Hasil Belajar Siswa Kelas XI Pada Materi Hukum Pascal - Tri Asih Apriliani; Herlina Usman; Novi Aulia Hikmawati (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
Research on the problem based learning model on Pascal's law material aims to determine student learning outcomes in class XII. This research is classroom action research that uses Kurt Lewin's model or method. Kurt Lewin's classroom action research model consists of several stages, namely planning, action, observation and reflection. In this research, two cycles of research were carried out. Model based learning is often called problem based learning. By providing problems, it is hoped that students can be active in searching for and finding solutions to the problems given. With problem-based learning, educators try to invite students to be active in learning activities. Based on the results of data analysis, it was found that this learning experienced an increase in the percentage of learning completion and an increase in the class average. So the percentage of students who do not complete has decreased. The data results in cycle I showed that student learning completeness was 82.35% and in cycle II it rose to 88.48%. In cycle II the average student score was 76.47 and in cycle II the average student score rose to 85.25%. Meanwhile, the percentage of student failure to complete in cycle I was 17.65% and in cycle II it decreased to 11.52%. From the data results it can be concluded that the use of model based learning in Pascal's law material for class XII students can improve student learning outcomes.